The world of Goya, 1746-1828 - Schickel, Richard; Time-Life Books (Amsterdam, [Netherlands] Time-Life Books, Inc., 1968)
Traces the life, career and paintings of the Spanish court painter, Francisco Goya, with information on the times in which he lived and other artists of that era.
Painter of the Spanish mind -- The apprentice years -- Making it in Madrid -- Painter to the king -- The passionate duchess -- Los Caprichos: society unmasked -- Witness to a holocaust -- The serene exile -- Chronology.
Includes bibliographical references (page 187) and index.
Keywords: Goya, Francisco -- 1746-1828.